EXPEDIENTE - v16n4 - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Fernandes; Valentim, Renata Patrícia Forain de; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2018)
EXPEDIENTE - v16n4